1995
DOI: 10.1016/0014-2999(95)00366-s
|View full text |Cite
|
Sign up to set email alerts
|

Carotid blood flow distribution, haemodynamics and inotropic responses following calcitonin gene-related peptide in the pig

Abstract: The sensory neuropeptide, calcitonin gene-related peptide (alpha-CGRP), has been implicated in the pathogenesis of migraine headache. The present study aimed to evaluate the effects of intracarotid infusions of human alpha-CGRP (10, 30 and 100 pmol/kg.min; n = 8), as compared to that of saline (4 times; n = 8) on haemodynamics and blood flow distribution within the carotid circulation of the anaesthetized pig, using the radioactive microsphere method. Furthermore, the effects of antimigraine drugs, dihydroergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is worthy of note that CGRP is a potent inotropic agent in rabbits, pigs as well as humans (Van Gelderen et al 1995; Bell & McDermott 1996), but not in rats (Ishikawa et al 1987; Bratveit et al 1991). This may explain the lack of effect of α‐CGRP on cardiac output in our study (fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy of note that CGRP is a potent inotropic agent in rabbits, pigs as well as humans (Van Gelderen et al 1995; Bell & McDermott 1996), but not in rats (Ishikawa et al 1987; Bratveit et al 1991). This may explain the lack of effect of α‐CGRP on cardiac output in our study (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among these neuropeptides, CGRP is considered as a biological marker in migraine pathogenesis ( Van Rossum et al , 1997 ; Goadsby et al , 2002 ; Hagner et al , 2002 ). Moreover, stimulation of trigeminal sensory neurones with electrical procedures or chemical substances, like capsaicin, releases endogenously stored CGRP ( Buzzi et al , 1995 ; Eltorp et al , 2000 ) that, in turn, dilates cranial vessels (Williamson & Hargreaves, 2001), including carotid arteriovenous anastomoses ( Van Gelderen et al , 1995 ). In addition, CGRP may also facilitate sensory nerve transmission between the first‐ and second‐order afferent input from these vessels during migraine headache ( Gulbenkian et al , 2001 ; Goadsby et al , 2002 ; Smith et al , 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that CGRP causes a positive inotropic effect in the atria of guinea-pig, rat and man [35] and ventricular trabeculae of pig [36] and man [37].…”
Section: Positive Inotropementioning
confidence: 99%